Fractionation And Environmental Risk Of Trace Metals In Surface Sediment Of The East China Sea By Modified BCR Sequential Extraction Method - Roy Andreas; Jing Zhang (Universitas Jenderal Soedirman, 2016)
Geochemical fractionation of Cadmium (Cd), Lead (Pb), Cobalt (Co), Zink (Zn), Iron (Fe) and Manganese (Mn) in sediment of the East China Sea were determined using four-stages of modified BCR sequential extraction method combination with ICP-MS. The total concentration of trace metals in sediment samples were in the following order: Fe >Mn>Pb> Zn > Co > Cd. Cd is present mainly in acid soluble fraction. Pb and Mn are in the group with presenting of easy reducible fraction and acid soluble fraction. Fe and Co were found in a group with mainly in residual fraction, while Zn was distributed in all four fractions. The highest contamination factors were found for Cd and Mn while the lowest were found for Fe and Co in almost station. The result showed low risk for Fe and Co in all station, Pb (except S2 and S3), Zn at S3,S6 and S7, and Mn at S1. A medium risk is indicated for Pb at S2 and S3, Zn at S1 and S5, and Mn at S2 and S6. A high risk showed for Zn at S2 and S4, and Mn at S4 and S5, while Cd at almost station (except S4) was very high risk.